A cross-sectional study on nurses' attitudes towards physical restraints use in nursing homes in Portugal - Ferrão, Sónia (2021)
© 2021 The Authors. Nursing Open published by John Wiley & Sons Ltd. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.